Growth-dependent haemolymph physiology in freshwater crayfish farmed in Western Australia - Mai, Van Ha (Curtin University, 2016)
Five experiments on crayfish under laboratory and outdoor field conditions were conducted to (1) establish relationships between moult stages and haemolymph osmolality (2) evaluate the interactions among size-dependent haemolymph ionic profile and physiology, feed ingestion and foregut evacuation rate and (3) evaluate the effects of abiotic and abiotic factors on the productivity of yabby populations. Moult stages significantly affected the haemolymph physiology, growth and health status. Zooplankton density and phosphorus influenced the yabby productivity.